Strategi Pengembangan Digital Marketing dan Personal Selling Halal Food di Kopi Telu Sawah View Pandaan Pasuruan - Ruhbatul A’fiah Diah Ayu Ningtyas; Muhammad Fahmul Iltiham; Sukamto; Muhammad Nizar (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2022)
In the working environment, the use of technology today is very beneficial for marketing activities. Companies can sell goods and services through a variety of platforms with good technology. Marketing campaigns use digital technology, or